Sick pay reforms and health status in a unionised labour market - Laszlo Goerke (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2016)
We theoretically analyse the effects of sick pay and employees' health on collective bargaining, assuming that individuals determine absence optimally. If sick pay is set by the government and not paid for by firms, it induces the trade union to lower wages. This mitigates the positive impact on absence. Moreover, a union may oppose higher sick pay if it reduces labour supply sufficiently. Better employee health tends to foster wage demands. If the union determines both wages and sick pay, we identify situations in which it will substitute wages for sick pay because adverse absence effects can be mitigated.
Keywords: D62; I13; I18; J22; J51; J52; 330; absence; employment; sick pay; trade union; wage determination